Plasma torch for supersonic plasma spray at atmospheric pressure - Caliari, F. R.; Miranda, F. S.; Reis, D. A.P.; Filho, G. P.; Charakhovski, L. I.; Essiptchouk, A. [UNESP] (Elsevier, 2016)
This work presents a plasma torch able to operate at supersonic regime with axial injection of feedstock. In contrast to commonly used linear scheme, the principal axis of the plasma torch is perpendicular to feedstock injection direction, which is aligned with coming out plasma jet. The plasma torch has slightly ascending current voltage characteristics and fixed arc length. Electrical, thermal and kinetic characteristics outlined from comparison with conventional linear plasma spray torches are intermediate between APS, HVOF and VPS. The plasma torch developed in this work has an elevated arc voltage (370 V) and low arc current (100 A), which contribute to increase the electrode life and decrease the arc voltage relative fluctuation (10%). According to in-flight particle monitoring the CoNiCrAlY particles were sprayed at 500 m/s and temperature of 2400 °C, whereas the 7%YSZ at 491–683 m/s and 2535–2636 °C.
Keywords: Atmospheric plasma spray; Axial injection; In-flight particle characteristics; Plasma torch; Supersonic plasma spray